The Effect of Different Surface Treatments on The Shear Bond Strength Between Flowable Composite and Glass Ionomer Cement - Manaf B. Ahmed (University of Mosul, College of Dentistry, 2023)
Aims: The study aims to evaluate the effect of different surface treatments on the shear bond strength between flowable composite and glass ionomer cement. Materials and Methods: 40 samples of glass ionomer cement were prepared by mixing the GIC under manufacturer instructions and applied inside a transparent ring measured 3mm in diameter and 2 mm in height. Then the samples were segmented into 4 groups, Group (1) as a control negative group without surface treatment, Group (2) with surface treated by 37% phosphoric acid, Group (3) surface treated by air abrasion with aluminum oxide particles, and Group (4) surface treated by polishing discs. Then Adper single bond 2 was placed over samples of groups (2,3,4) and light cured, then another transparent ring measured 3 mm in diameter and 6 mm in height was applied over each GIC disc, and flow the flowable composite incrementally into two layers, each layer as 3mm and cured by light cure. Then remove the transparent rings to obtain the two bonded materials, GIC, and flowable composite as one sample, then measure the bond strength between the two materials for all groups by using the universal testing machine. Data were analyzed by using One-Way Analysis of Variance and Tukey's test. Results: A significant difference is observed in shear bond strength (SBS) of the groups (P<0.05). Group (3) showed the high SBS and Group (1) showed the lowest SBS and there is a significant difference between all the groups in relation to SBS. The high difference between Gp(3) and Gps(1,4) whereas the lowest difference is between Gp(2) and Gp(4). Conclusions: Within the limitation of this study, the treatments of surface increase the shear bond strength between GIC and flowable composite, and high bond strength is obtained by air abrasion technique then followed by acid etching and polishing disc respectively.